The impact of low doses of gamma rays on Chemical and hematological parameters for healthy people and diabetes in Thi Qar province - Murad, Assel M. Radhi; Rashed, Jabbar; İLYAS İNCİ (University of Thi-Qar Journal of Science, 2023)
Abstract The objective of this study is to explore the effect of gamma irradiation on the hematological and biochemical parameters of complete blood counts for diabetic and healthy people. A total of 20 blood samples were collected from people with diabetes, and 20 samples were collected from healthy people of different ages.  The samples were analyzed before and after exposing to irradiation (0.5 mCi Cs-137 Gamma-ray standard source) using a Hematology analyzer to determine the hematological and biochemical parameters. Significant changes were observed between the control samples before and after exposing to irradiation. The results showed a significant change in the number of Red Blood Cells at 18.863 mGy/hr. compared with the control sample in healthy and unhealthy people from 4.47x106 μL to 1.82x106 μL and from 4.32x106 μL to 1.05x106 μL, respectively. The results also showed a significant change in all hematological and biochemical parameters such as WBC, PLT, Hb, Hct, Mcv, McH, and HcHc after exposing to irradiation, especially at a high dose rate of more than 5 mGy/hr. The obtained results are in a good agreement with the data that were recommended by   recognized international organizations and agencies such as the EPA, IAEA, WHO, UNSCEAR, and ICRP.